Lead up to Scopus: Meningkatkan Pengelolaan OJS, Manajemen Review dan Kualitas Artikel Berbasis Standar Jurnal Internasional pada JSR (Jurnal Sosiologi Reflektif) - Dwi Nur Laela Fithriya (Jurnal Humanitaria Jurnal Ilmu Sosial dan Humaniora, 2024)
Accreditation is currently one of the important aspects in measuring the reputation of a scientific journal. As the presence of scientific journals is intended to support the academic achievements of lecturers and researchers, journals must inevitably make efforts to make various changes and improvements to achieve the best reputation, especially in the international scope. This study tries to examine more deeply why JSR has not been able to increase its score from the results of Sinta accreditation in 2018 and 2020 in terms of OJS management, review management and article quality and what efforts can be made to improve the performance of OJS management, review management and article quality to meet international standards (Scopus). This study uses a qualitative approach, with data collection techniques in the form of observation (direct observation), in-depth interviews with journal managers, and FGD. Based on the results of the research and discussion that have been presented by the author, it can be concluded that the Reflective Sociology Journal (JSR) still faces various challenges and problems. These challenges and problems come not only from external but also internal. From the external, JSR is faced with the fact that national and international accreditation requires JSR to make improvements in OJS management, review management and most importantly, improving the quality of articles. While from the internal, JSR faces challenges and problems also related to OJS management, review management and article quality. Keywords: Journal; Accreditation; Scopus